The Relationship of Mother's Knowledge Level and Occupation with Feeding Patterns of 12-60 Months Children in Melapeh New Village Kutai Barat Regency - Presensia, Presensia; Wiyadi, Wiyadi; Suryani, Heni (Rifa'Institute, 2023)
Background: Diet in toddlers plays an important role in the growth process in toddlers, because foods that contain lots of nutrients can support the child's growth and development process. So, there is malnutrition in toddlers. The level of knowledge and work of the mother will greatly affect the pattern of feeding the child, the mother's ignorance of the pattern of feeding the child will result in errors in the selection of food ingredients so that it will cause malnutrition. Objective: To determine the relationship between mother's level of knowledge and occupation with feeding patterns in children aged 12-60 months in Melapeh Baru Village. Methods: This type of research is an observational study using a Cross Sectional approach. The population of mothers with toddlers aged 12-60 months in Melapeh Baru Village in January 2021 amounted to 124 toddlers. Results and Discussion: The test results obtained that there was a relationship between the level of mother's knowledge (p-value = 0.035) and work (p-value = 0.000) with eating patterns in children aged 12-60 months. Conclusion: There is a relationship between the level of knowledge and mother's occupation with feeding patterns in children aged 12-60 months in Melapeh Baru Village